Ultrastructural and physicochemical characterization of pH receptive chlorhexidine‐loaded poly‐L‐glycolic acid‐modified orthodontic adhesive. Issue 3 (30th October 2021) - Kamran, Muhammad Abdullah; Alshahrani, Abdulaziz; Alnazeh, Abdullah A.; Udeabor, Samuel Ebele; Qasim, Muhammad; Alshahrani, Ibrahim
Abstract: This study aims to evaluate the feasibility of chlorhexidine (CHX)‐loaded poly‐L‐glycolic acid (PLGA) nanoparticles as a modifier of a commercial orthodontic adhesive via the assessment of physicochemical, biological, and mechanical properties at tooth‐bracket interface. CHX‐loaded PLGA nanoparticles were synthesized using double emulsion‐solvent evaporation method and characterized using transmission electron microscopy and Raman analysis. CHX‐loaded PLGA nanoparticles in Transbond XT orthodontic adhesive were prepared using two different concentrations of the CHX (25 and 50%) and characterized for degree of conversion (DC), antimicrobial, and cytotoxicity testing. Bonded specimens were tested for shear bond strength (SBS) and adhesive remnant index (ARI) at tooth‐bracket interface. The synthesized PLGA nanoparticles averaged between 60 and 80 nm in size. After loading CHX inside PLGA nanoparticles, the morphology of the PLGA nanoparticles was considerably changed. Orthodontic bracket bonded with 25% CHX‐loaded PLGA‐modified adhesive demonstrated DC scores similar to control group. Both 25 and 50% CHX‐loaded PLGA‐modified adhesive specimens showed higher antibacterial activity against S. mutans compared to control group. The least mean SBS values were exhibited by 50% CHX‐loaded PLGA‐modified adhesive samples, while a statistically significant difference was observed in the mean ARI values among all study groups at all‐time points ( p  = .018). This study indicates that the addition of CHX‐loaded PLGA nanoparticles in Transbond XT achieved stable bonds with enhanced antimicrobial and mechanical properties. Abstract : PLGA tends to release high amount of chlorhexidine in low pH microenvironments. The 50% CHX‐loaded PLGA‐modified adhesive specimens showed more profound antibacterial activity against Streptococcus mutans . The addition of CHX‐loaded PLGA nanoparticles in Transbond XT provided safe and efficacious modification of orthodontic adhesive.